Association Between Hypertensive Disorders of Pregnancy and Dementia: a Systematic Review and Meta-Analysis. Issue 2 (8th November 2022) - Schliep, Karen C.; Mclean, Hailey; Yan, Bin; Qeadan, Fares; Theilen, Lauren H.; de Havenon, Adam; Majersik, Jennifer J.; Østbye, Truls; Sharma, Surendra; Varner, Michael W.
Abstract : Background: Prior meta-analyses report a 2- to 4-fold increased risk of later cardiovascular disease among women with a history of hypertensive disorders of pregnancy (HDP). Given HDP's vascular underpinnings, it is hypothesized to also be a risk factor for later dementia. We aim to summarize the evidence for the impact of HDP on dementia and consider unique associations between HDP and dementia subtypes. Methods: Observational studies on the relationship between HDP and dementia were identified from online electronic databases to July 1, 2021 (PROSPERO identifier: CRD42020185630). We included observational studies published in English. Exposure among women was any HDP and HDP subtypes: gestational hypertension, preeclampsia/eclampsia, or other/unspecified HDP. Outcome was any dementia and dementia subtypes: Alzheimer's disease, vascular dementia, or other/unspecified dementias. Results: For our primary analyses, we included 5 cohort studies with a total of 183 874 women with and 2 309 705 women without HDP. Pooled analysis found a 38% higher risk of all-cause dementia among women with, versus without, any type of HDP (adjusted hazard ratio, 1.38 [95% CI, 1.18–1.61]; P <0.01). When examining association by HDP and dementia subtypes, we found that women with, versus without, any type of HDP had over a 3-fold higher risk of vascular dementia (adjusted hazard ratio, 3.14 [95% CI, 2.32–4.24]; P <0.01). Conclusions: Our findings indicate that maternal history of HDP is an important risk factor for later development of vascular and all-cause dementia. Further research among more racially/ethnically diverse populations quantifying HDP's effect on all-cause dementia, and specifically vascular dementia, is warranted.